Acceptability of the Transitional Wearable Companion “+me” in Typical Children: A Pilot Study - Sperati, Valerio; Özcan, Beste; Romano, Laura; Scaffaro, Simone; Moretta, Tania; Turturo, Giada; Aliberti, Maria Nicoletta; Guidetti, Vincenzo; Baldassarre, Gianluca (Frontiers in Psychology, 2019)
This work presents the results of the first experimentation of +me –the first prototype of Transitional Wearable Companion– run on 15 typically developed (TD) children with age between 8 to 34 months. +me is an interactive device looking like a teddy bear that can be worn around the neck, has touch sensors, can emit appealing lights and sounds, and has input-output contingencies that can be regulated with a tablet via Bluetooth. The participants were engaged in social play activities involving both the device and an adult experimenter. +me was designed with the objective of exploiting its intrinsic interestingness as an attractive toy to stimulate social interactions (e.g. eye contact, turn taking, imitation, social smiles), an aspect potentially helpful in the therapy of Autism Spectrum Disorders (ASD) and other Pervasive Developmental Disorders (PDD). The main purpose of this preliminary study is to evaluate the general acceptability of the toy by TD children, observing the elicited behaviours in preparation of future experiments involving children with ASD and other PDD. First observations, based on video recording and scoring, show that +me stimulates a good social engagement in TD children, especially when their age is higher than 24 months.